Effects of the irrigation regimes on grapevine cv. Bobal in a Mediterranean climate: I. Water relations, vine performance and grape composition - Pérez-Álvarez, Eva P.; Intrigliolo, Diego S.; Vivaldi, Gaetano A.; García-Esparza, María J.; Lizama, V.; Álvarez, Inmaculada (Elsevier, 2021)
Climate change scenarios are predicting an increase in temperature as well as more scarce and torrential rainfall episodes. Due to this, an imbalance between grape technological and phenolic maturity is being observed detrimentally affecting grapes composition. In semi-arid areas, irrigation management is a main field practice to influence grape ripening. The goal of the present study was to investigate in Vitis vinifera L. cv. Bobal grapevine responses to three watering regimes: (I) Rainfed, (II) deficit irrigation (DI) replacing only 35% of the estimated crop evapotranspiration (ETc) and (III) full irrigation (FI) replacing 100% ETc. In the mid-summer, rainfed grapevines showed different degrees of water stress determined by midday stem water potentials (Ψstem) ranging from −1.1 to −1.4 MPa depening on the season. Rainfed plants had in all seasons less vigor and production and, at harvest, higher concentrations of total soluble solids (TSS) and grape phenolics compounds, as well as lower pH, with respect to the other water regimes studied. DI grapevines, generally, had intermediate values between Rainfed and FI, which presented extreme values of the studied parameters respect to Rainfed. The effects observed on grape color parameters and phenolic compounds with the Rainfed regime were mainly due to a dehydration of the berry, which lowered the yield and the weight of the berry compared to the irrigated treatments. The lower TSS accumulation in the DI berries with respect to the Rainfed, will favor obtaining wines with lower alcohol content, currently more demanded by the consumers. Besides, despite the differences obtained between water regime treatments in the TSS accumulation, the extractability of the anthocyanins was similar, which is interesting since anthocyanin extraction from grapes is prerequisite to the formation of stable red wine pigments. Although the most convenient irrigation strategy might depend to the wine style to be obtained, DI is a strategy that can help to close the gap in the imbalance between the technological and phenolic maturity, positively affecting vine yield and performance with respect to the rainfed strategy.